Entrepreneurial intentions of business students in Malaysia: The role of self-confidence, educational and relation support. Issue 1 (20th February 2017) - Gelaidan, Hamid Mahmood; Abdullateef, Aliyu Olayemi
Abstract : Purpose: The purpose of this paper is to empirically examine the effects of relational support, educational support and self-confidence on entrepreneurial intentions of undergraduate business students in a university. Design/methodology/approach: To empirically validate the conceptual model and test the hypothesised relationships, the authors collected data from 227 business students at an AACSB-accredited university in Malaysia through random sampling. Findings: The results were based on analyses from structural equation modelling using the SmartPLS software. The findings show that entrepreneurial intention of business students is significantly influenced by educational and relational support; however, the moderating effects of self-confidence in the relationship between educational support, relational support and entrepreneurial intention are not significant. The paper clearly shows that relational and educational supports are two important factors that can influence the entrepreneurial intention of university students. Originality/value: This research contributes to literature on entrepreneurial motivations and intentions through its empirical findings of the hypothesised relationships. It theoretically contributes to existing knowledge by integrating relevant themes from entrepreneurial motivations theory and the theory of planned behaviour. Finally, it offers alternative recommendations to university authorities and policymakers about business students' entrepreneurship intention.